Manejo de leguminosas de coberturas con fines de conservar y mejorar las propiedades de suelos - Garcia Arévalo, Angel Miguel (2012)
In recent years, coverage crops in association with others crops are expanding rapidly, particularly those leguminous covers because of the benefits it brings. This is why we developed this research work at Seasonal Station “Choclino”, where the characteristics of the soils are highly acidic and initially dominated by “Shapumba” (Pteridium aquilinum); the objective is: Determine the contributions of biomass and nutrients and the effect on soil physical properties. It was used the “Randomized Block Design”, with 04 treatments (cover crops under study) and 03 replications or blocks, the comparison of means was performed by Duncan’s test (α = 0.05). The result obtained show significant differences in the total biomass (foliar and root) based on the dry matter, Centrosema macrocarpum being superior with10.09 tn ha - 1 , in comparison with other treatments, which is reflected in the contribution and recycling of nutrients. Also we determined the effect of the physical proprieties of soil, where there were not differences between treatments, which indicates that the management of coverage is an alternative for the conservation of soil proprieties to a lesser or greater degree depending the kind of coverage to use.